Argon ion implantation inducing modifications in the properties of benzene plasma polymers - Rangel, E. C.; Cruz, N. C.; Santos, DCR; Algatti, M. A.; Mota, Rogério Pinto [UNESP]; Honda, R. Y.; Silva, PAF; Costa, M. S.; Tabacniks, M. H. (Elsevier B.V., 2002)
Benzene plasma polymer films were bombarded with Ar ions by plasma immersion ion implantation. The treatments were performed using argon pressure of 3 Pa and 70 W of applied power. The substrate holder was polarized with high voltage negative pulses (25 kV, 3 Hz). Exposure time to the immersion plasma, t, was varied from 0 to 9000 s. Optical gap and chemical composition of the samples were determined by ultraviolet-visible and Rutherford backscattering spectroscopies, respectively. Film wettability was investigated by the contact angle between a water drop and the film surface. Nanoindentation technique was employed in the hardness measurements. It was observed growth in carbon and oxygen concentrations while there was decrease in the concentration of H atoms with increasing t. Furthermore, film hardness and wettability increased and the optical gap decreased with t. Interpretation of these results is proposed in terms of the chain crosslinking and unsaturation. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: plasma polymer; plasma immersion ion implantation; wettability; hardness